GAME AS A FRAGMENT OF A LESSON IN PRIMARY SCHOOL - Bokhonko, Mariana (Global Prosperity, 2022)
The article analyzes the role of play as one of the elements of the lesson in primary school. The characteristic features of game methods are named and how they differ from traditional methods. It is noted that the game method is a way of interaction between teacher and students (student), due to the game, which leads to the implementation of didactic tasks and learning objectives. The following game methods are distinguished: games-exercises, game discussion, game situation, educational-game game. The conditions of the game that the student and the teacher must follow to achieve the appropriate results are analyzed. During the preparation and implementation of the game method of learning, it is necessary to comply with the following basic requirements: choosing the theme of the game, defining the purpose and objectives of preparing and conducting the game (informing students of the game, preparing visuals, conducting games, summarizing). The article presents the structure of the developed game activity, which includes the following components: motivational, indicative, executive, control and evaluation. Several games on the development of students' emotions in primary school lessons are considered, the purpose of which is to enable the teacher to understand the emotional state of students through facial expressions, gestures, pantomime, movements and mood; development of the ability to regulate the emotions and feelings of children; fostering positive emotional relationships between students and teachers. In the process of research, it is proved that the effective use of the game as a fragment of the lesson in primary school gives a proper result of educational activities